Effect of Plant Nutrients on Fruit Yield and Quality of Cavendish Banana (Musa sp.) cv. ‘Grand Naine’ - Chalise, Basant; Shrestha, Arjun Kumar; Srivastava, Arvind; Tripathi, Kalyani Mishra (Nepalese Horticulture, 2023)
A field experiment was conducted to evaluate the effect of plant nutrients on yield and fruit quality of ‘Grand Naine’ banana under alkaline soil conditions for the two cropping seasons 2020-2021 and 2021-2022 at Directorate of Agricultural Research (DoAR), Khajura. The trial was laid out in a randomized complete block design consisting of seven treatments replicated three times having four plants in an experimental plot. Planting of tissue culture banana was done at 2×2 m spacing on 4th July 2020 and suckers selected from the same plant on the same date were taken as the first ratoon crop. Farmyard manure was applied at four, chemical fertilizers at six, and micronutrients at three installments. The pooled results revealed that the longest bunch (114.30 cm), the highest number of hands (10.08) and finger number per bunch (185.80) and second hand (21.50), the heaviest bunch (25.74 kg) and second-hand weight (3.28 kg), the highest finger length (21.08 cm), diameter (3.85 cm) and weight (156.20 g) and bunch yield (64.35 mt/ha), the highest TSS (20.20%), TSS: TA ratio (47.10) and total sugar (12.55%) and the lowest TA (0.43%) were registered in T3 (20 kg FYM, 250:250:350 g NPK along with foliar spray of four types of micronutrients viz. Zn, Fe, Cu and B at 3rd 5th and 7th months of planting. Hence, from the study banana growers are recommended to use FYM, chemical fertilizers along with a foliar spray of micronutrients, at least three times in the vegetative growth stage of bananas for higher yield and improved quality of fruits.